Effect of sprouting whole wheat grain on the sensory quality, physicochemical properties, and antioxidant activity of cupcakes - Waheeba Elfaki Ahmed; Islam Ragab; Mohamed G.E. Gadallah; Raghad M. Alhomaid; Mona S. Almujaydil (Applied Food Research, 2024)
This study investigated the effects of sprouting wheat grain on the nutritional and sensory properties of cupcakes. Wheat grain was sprouted for different durations (1, 3, and 5 days) to enhance its nutritional benefits. The results showed that sprouting increased the bioavailability of minerals such as Zn, Ca, Mg, Cu, and Mn compared to unsprouted wheat flour. Additionally, sprouted wheat flour (SWF) exhibited reduced levels of wet gluten, dry gluten, and gluten indices, which made it more suitable for cake making. The antioxidant capacity and total phenolic content of the sprouted wheat flour increased significantly during the 5-day sprouting period. Moreover, cupcakes made from wheat flour sprouted for 1 and 3 days had improved specific volume compared to the control. However, the lightness of the cupcakes gradually decreased when sprouting was performed on days 1 and 5.In terms of sensory evaluation, cupcakes made from wheat flour sprouted for 1 day were found to be significantly more acceptable compared to the control. However, there was no significant difference in acceptability between the control cupcakes and those made from wheat flour sprouted for 3 days. Importantly, all samples of sprouted wheat flour and cupcakes tested in this study were found to have no detectable contamination of E. coli. Sprouting wheat grain for up to 3 days can enhance the nutritional composition, increase antioxidant levels, and produce acceptable and healthier cupcakes. These findings suggest that sprouted wheat flour can be a beneficial ingredient for baking applications, providing improved nutritional value and sensory attributes.